Spatial cytotoxic and memory T cells in tumor predict superior survival outcomes in patients with high‐grade serous ovarian cancer. (5th May 2021) - Zhang, Guodong; Xu, Qing; Zhang, Xiangyun; Yang, Moran; Wang, Yiying; He, Mengdi; Lu, Jiaqi; Liu, Haiou
Abstract: Although the association between tumor‐infiltrating CD3 + T and CD8 + T cells and superior survival in high‐grade serous ovarian cancer (HGSOC) has been observed, the different spatial localization of tumor‐infiltrating lymphocytes (TILs) possesses heterogeneous effects. We performed localized measurements in 260 HGSOC from 2 independent cohorts represented in tissue microarray format to determine the localized expression pattern and clinical significance of CD3 + T, CD8 + T, and CD45RO + cells in HGSOC. Different density of spatial localization of CD3 + T, CD8 + T, and CD45RO + cells exhibited heterogeneous association with OS. The combination of the center of the tumor and invasive margin localized CD8 + T cells (CD8 CT&IM ) with the same margin localized CD45RO (CD45RO CT&IM ) was the most robust prognostic predictor. Immune score (IS) was constructed by integrating FIGO stage with CD8 CT&IM and CD45RO IM&CT and had the best prognostic value in HGSOC. The low‐, intermediate‐, and high‐IS groups were observed in 44.7%, 41.6%, and 13.7% of patients, respectively. Low‐IS identified patients were at higher risk of death compared to high‐IS identified patients (HR = 12.426; 95% CI 5.317–29.039, p  < 0.001); meanwhile, we evaluate the RMSTs over 10 years of follow‐up and obtained RMST values of 104.09 months (95% CI 96.31–111.87 months) in the high‐IS group, 75.26 months (95% CI 59.92–90.60 months) in the intermediate‐IS group, and 48.68 months (95%CI 38.82–58.54 months) in the low‐IS group. In general, spatial localization can modulate the clinical effects of TILs in HGSOC. Thus, the spatial expression of CD8 and CD45RO could aid clinicians to determine the follow‐up plan of patients with HGSOC. Abstract : Infiltrating T cells in distinct areas associated with different clinical outcomes, and cytotoxic and memory T cells combing clinical characteristic can efficiently predict survival in clinical practice.